The safety of concomitant transcatheter aortic valve replacement and percutaneous coronary intervention: A systematic review and meta-analysis. Issue 48 (December 2017) - Yang, Yong; Huang, Fang-Yang; Huang, Bao-Tao; Xiong, Tian-Yuan; Pu, Xiao-Bo; Chen, Shi-Jian; Chen, Mao; Feng, Yuan
Abstract: Background: TAVR is a rapidly spreading treatment option for severe aortic valve stenosis. Significant coronary artery disease (CAD) is present in 40% to 75% of patients undergoing TAVR. However, when to treat the concomitant coronary artery lesions is controversial. Methods: This is a systematic review comparing concomitant PCI and TAVR versus staged PCI and TAVR. The OVID database was systematically searched for studies reporting PCI in patients undergoing TAVR. A random effects model was used to calculate the pooled odds ratio (OR) with 95% confidence intervals. Results: Four observational studies and a total of 209 patients were included in this analysis. Overall 30-day mortality was similar between concomitant PCI and TAVR versus staged PCI and TAVR [OR: 1.47 (0.47–4.62); P = .51], renal failure was not significantly different between both groups [OR: 3.22 (0.61–17.12); P = .17], periprocedural myocardial infarction was not different between the 2 groups [OR: 1.44 (0.12–16.94); P = .77], life-threatening bleeding did not differ between both groups [OR: 0.45 (0.11–1.87); P = .27], and major stroke also was not significantly different [OR: 3.41 (0.16–74.2); P = .44]. Conclusion: These data did not show a significant difference in short-term outcomes between concomitant PCI and TAVR versus staged PCI and TAVR.